Anticonvulsant Effects of Fuzi Total Alkaloid on Pentylenetetrazole-Induced Seizure in Mice - Bingjin Li; Fang Tang; Liang Wang; Lei Liu; Jing Zhao; Yang Zhou; Yinuo Wang; Yunong Song; Yuxin Li; Ranji Cui (Elsevier, 2013)
We investigated the anticonvulsant effect of acute Fuzi total alkaloid (FTA) in seizure induced by the GABAA-receptor antagonist pentylenetetrazole (PTZ). FTA significantly increased the seizure latency and decreased the mortality in PTZ-treated mice. Administration of PTZ increased c-Fos expression in the hippocampus, medial prefrontal cortex, and piriform cortex; and this PTZ-induced effect was inhibited by FTA in a dose-dependent manner. Furthermore, the effects of FTA on PTZ-induced seizure and c-Fos expression were reversed by the GABAA/benzodiazepine receptor-selective antagonist flumazenil. These findings suggest that the anticonvulsant effects of FTA may be related to modulation of GABAA-benzodiazepine receptor complex. Keywords:: c-Fos, seizure, pentylenetetrazole